Stem wound healing is dependent upon bark and trunk growth rates in Brazilian savanna - Hoffmann, William A.; Flake, Samuel W.; Rossatto, Davi R. [UNESP]; De Antonio, Ariadne C. [UNESP]; Durigan, Giselda; Abreu, Rodolfo C. R. (Springer Nature, 2024)
Key message: Stem wounds heal most quickly in fast-growing trees. Despite slower growth among savanna species, their wound closure matches forest species, owing to a positive influence of investment in bark production. Abstract: Stem wounding by fire poses a survival risk to trees in frequently burned environments. Ability to close wounds quickly is important for minimizing exposure of the stem to rot, insects, and future fires, so we investigated factors influencing rates of wound closure. We hypothesized that the rate of wound closure is positively correlated with growth rate, negatively correlated with wood density, and greater for savanna species than forest species. To test these hypotheses, we induced mechanical damage in trunks of 36 tree species in fire-suppressed savanna in southeastern Brazil, and measured subsequent rates of wound closure. There was a strong positive correlation between wound closure and diameter growth, both within and among species. Growth rate varied among functional types, being greatest among forest specialists and lowest among savanna specialists, while the opposite pattern was found for relative bark thickness. Despite differences in growth rate, there was no difference in wound closure among functional types. This apparent inconsistency occurs because of a positive correlation between relative bark thickness and rate of wound closure, after controlling for growth rate. Wound closure was most strongly predicted by the rate of bark increment, which is determined by growth rate and relative bark thickness. There was no effect of wood density on wound closure. These findings enhance our understanding of wound closure dynamics in trees and highlight the importance of growth rate and bark characteristics in determining the ability of trees to recover from damage.
Keywords: Bark; Fire; Forest; Savanna; Wounding